Solitary fibrous tumor - Davanzo, Brian; Emerson, Robert E.; Lisy, Megan; Koniaris, Leonidas G.; Kays, Joshua K. (Translational Gastroenterology and Hepatology, 2018)
Solitaryfibrous tumor (SFT) is a rare tumor of mesenchymal origin that account for lessthan 2% of all soft tissue masses. Initially identified in the pleura, SFT hasbeen identified in multiple anatomic locations and can arise anywhere in thebody. The varying histologic features along with non-specific means ofidentification have led SFT to be associated with several different names. Overthe last several decades, sustained advances through research and technologyhave led to more reliable methods for differentiating this distinct soft tissuetumor. Advances specifically in immunohistochemistry and molecular diagnosticshave identified CD34 as the most consistent marker in SFT, however even this lacksspecificity to conclusively narrow down the broad differential for exactidentification. More recently the discovery of the NAB2-STAT6 fusiongene has led to more precise diagnosis of SFT. Like many other soft tissuetumors, surgical management is the mainstay of treatment for SFT with emphasison obtaining tumor-negative margins. Radiation therapy and chemotherapyregimens have not demonstrated global effectiveness, and thus no standardizedtreatments have been identified. Given the rarity of SFT and current supportiveevidence for therapies, management should be focused on tumor extirpation.Nonetheless, individualized therapy, determined within a multidisciplinarysetting should be considered.